Hubungan Antara Self Disclosure dengan Interpersonal Trust pada Pasangan Dewasa Awal yang Menjalani Long Distance Relationship (LDR) - Alvina Tri Septiani; Ratriana Yuliastuti Endang Kusumiati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Long distance relationship (LDR) is a form of romantic relationship where two people are separated by physical distance which makes it difficult for both to establish closeness within a certain period. Of course, living in a long-distance relationship is not an easy thing if there is no self-disclosure and interpersonal trust in the relationship. Openness is one of the factors that play an important role in forming interpersonal trust. Openness arises because of the trust between partners and this encourages them to feel comfortable in sharing all kinds of information about themselves to their partners. The purpose of this study is to determine the relationship between self-disclosure and interpersonal trust in early adult couples who undergo long-distance relationships. This study uses a correlational quantitative approach with 120 respondents. The sampling technique in this study used accidental sampling. The results of the correlation coefficient analysis obtained are 0.837 and the significance value of the correlation r is 0.000 (p <0.05). The effective contribution between self-disclosure and interpersonal trust is 70%. So it can be concluded that there is a positive relationship between self-disclosure and interpersonal trust, meaning that the higher the self-disclosure, the higher the level of interpersonal trust in early adult couples who undergo long-distance relationships, and vice versa